2011
DOI: 10.1039/c1np00042j
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for degradation of lignin in bacteria and fungi

Abstract: Lignin is a heterogeneous aromatic polymer found as 10-35% of lignocellulose, found in plant cell walls. The bio-conversion of plant lignocellulose to glucose is an important part of second generation biofuel production, but the resistance of lignin to breakdown is a major obstacle in this process, hence there is considerable interest in the microbial breakdown of lignin. White-rot fungi are known to break down lignin with the aid of extracellular peroxidase and laccase enzymes. There are also reports of bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
674
2
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 812 publications
(724 citation statements)
references
References 126 publications
9
674
2
9
Order By: Relevance
“…Oxalic acid (10) has been observed previously as a metabolite of microbial lignin oxidation. 8,20 For the background reaction in the presence of KO2 only, the only product peaks that could be detected by GC-MS were small amounts of vanillic acid (1) and oxalic acid (10), as shown in Figure 3.…”
Section: Proteomic Analysis Of Sphingobacterium Sp T2mentioning
confidence: 99%
“…Oxalic acid (10) has been observed previously as a metabolite of microbial lignin oxidation. 8,20 For the background reaction in the presence of KO2 only, the only product peaks that could be detected by GC-MS were small amounts of vanillic acid (1) and oxalic acid (10), as shown in Figure 3.…”
Section: Proteomic Analysis Of Sphingobacterium Sp T2mentioning
confidence: 99%
“…The catabolic lignin degradation pathway and the corresponding gene clusters were well studied in Sphingomonas paucimobilis SYK-6 using various lignin derived biaryls and monoaryls (Masai et al 2007). It was clear that bacteria mineralized lignin via protocatechuic acid 4, 5-cleavage pathway and the multiple 3MGA catabolic pathways which may be more significant on lignin degradation than previous thought (Bugg et al 2011). Considering the other advantages, including fast doubling time and easier gene manipulation, the bacterial system could be a better candidate in bio-conversion of lignocellulosic biomass.…”
Section: Introductionmentioning
confidence: 77%
“…In contrast to white rot and brown-rot fungi, several bacterial species belonged to actinomycetes, a-proteobacteria and c-proteobacteria also have capability to degrade lignin (Bugg et al 2011). The catabolic lignin degradation pathway and the corresponding gene clusters were well studied in Sphingomonas paucimobilis SYK-6 using various lignin derived biaryls and monoaryls (Masai et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, although it has been suggested that the white rot type of lignin decay evolved in the MRCA of Auriculariales and more derived Agaricomycetes in the Permian, alternate mechanisms of lignin degradation may well have evolved deeper in the phylogeny. Furthermore, although white rot Agaricomycetes are the most studied group of wood decay fungi, other fungal (100-107) and bacterial (101,102,(108)(109)(110)(111)(112)(113)(114) lineages are either known lignin degraders or show some enzymatic capability for lignin decay, although the phylogenetic breadth, evolutionary origins, and degradative capacities of these lineages are far less understood. Taken together, there appears to have been no shortage of options available for the decomposition of lignified tissue in the pre-Permian world.…”
Section: Resultsmentioning
confidence: 99%